Endocrine and non-endocrine causes of fatigue in adults with Neurofibromatosis type 1 - Rosenberg, Anna G. W.; Mochèl, Ké; Hähner, Lorena M.; Ruules, Lara; Davidse, Kirsten; Bos-Roubos, Anja G.; van Dijk, Sarah A.; Zillikens, M. Carola; Taal, Walter; van der Lely, Aart J.; de Graaff, Laura C. G. (Frontiers in Endocrinology, 2024)
Context: Neurofibromatosis type 1 (NF1) is a complex system disorder, caused by alterations in RAS pathways. NF1 adults often suffer from chronic and severe fatigue, for which they are frequently referred to Internal Medicine/Endocrinology. Seeking medical help often leads to (invasive) diagnostic procedures. To prevent the personal and financial burden of this disabling fatigue, it is crucial to know the causes. Objective: To explore somatic causes and provide practical recommendations for the approach to fatigue in adults with NF1.Design: Cross-sectional. All adults with NF1 (N = 133) who visited our Endocrinology department underwent a systematic health screening, including a medical questionnaire, structured interview, complete physical examination, biochemical measurements and additional tests if indicated. Main Outcome Measure: Prevalence of endocrine and non-endocrine health problems between NF1 adults with and without fatigue. Results: In our cohort, 75% of NF1 adults experienced fatigue. The most frequent endocrine disorders were vitamin D deficiency (28%), obesity (18%) and hypothyroidism (8%). The most frequent non-endocrine internal disorder was high blood pressure (42%). None of the disorders differed significantly between adults with and without fatigue. Conclusions: Endocrine and non-endocrine disorders were equally present in our cohort of NF1 adults with and without fatigue. This suggests that the high prevalence of fatigue in NF1 adults is not explained by these somatic disorders. An alternative explanation for fatigue might be deficits in cognitive functioning and other neuropsychological processes in NF1. Based on our results and review of the literature, we provide a clinical algorithm for the approach to fatigue in NF1 adults, including somatic and psychological assessment.